Impact of health-related quality of life on survival after dialysis initiation: a prospective cohort study in Korea - Jeonghwan Lee; Yong Chul Kim; Soie Kwon; Lilin Li; Sohee Oh; Do Hyoung Kim; Jung Nam An; Jang-Hee Cho; Dong Ki Kim; Yong-Lim Kim; Yun Kyu Oh; Chun Soo Lim; et al. (The Korean Society of Nephrology, 2020)
Background : The effect of each health-related quality of life (HRQOL) component on hemodialysis prognosis has not been well studied. We aimed to investigate the clinical factors associated with HRQOL and the effect of HRQOL after dialysis initiation on long-term survival in an Asian population. Methods : A total of 568 hemodialysis patients were included from a nationwide prospective cohort study. HRQOL was evaluated using the Kidney Disease Quality of Life (KDQOL) Short FormTM 1.3 at 3 months after dialysis initiation. The effect of each KDQOL item score on mortality was analyzed. Multivariable Cox analysis was performed after adjusting for age, sex, modified Charlson comorbidity index, and causes of primary kidney disease. Results : Old age, diabetes mellitus, high comorbidities, and low serum albumin levels were associated with poor physical health status. Decreased urine output was associated with both poor physical and mental health status. The scores of 3 indices in the kidney disease domain (effect of kidney disease, social support, and dialysis staff encouragement) showed significant associations with mortality, as did the 3 indices (physical function, physical role limitation, and body pain) in the physical health domain. Neither the 4 indices in the mental health domain nor the mental composite score showed a significant association with mortality. However, a high physical composite score was associated with decreased overall patient mortality (P = 0.003). The effect of physical composite score on survival was prominent among young or middle-aged groups. Conclusion : Poor physical health status 3 months after hemodialysis start correlates significantly with overall mortality.